2019
DOI: 10.20517/2394-5079.2018.104
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase promoter mutations in hepatocellular carcinogenesis

Abstract: Through several studies exploiting next-generation sequencing, we are obtaining a clearer picture of the complex genetic and molecular landscape of hepatocellular carcinoma (HCC). Consistent with the findings of other cancer types, telomerase reverse transcriptase (TERT) promoter mutations have been frequently reported in HCC. C228T and C250T are two major types of hot spot mutations in the TERT promoter region. Besides, in hepatitis B virus (HBV)-related HCC cases, the TERT promoter is recurrently interrupted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…The major risk factors for HCC include liver cirrhosis, hepatitis B or C virus infection, alcohol abuse, nonalcoholic steatohepatitis, and metabolic disease. The mutation landscape in liver carcinogenesis is reportedly complicated, involving a number of pathways as well as somatic mutations in a multitude of genes [ 2 , 3 , 4 ]. Among the genetic alterations, telomerase reverse transcriptase ( TERT ) promoter mutations were reported to occur early and most frequently, affecting approximately 30–60% of all HCC patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major risk factors for HCC include liver cirrhosis, hepatitis B or C virus infection, alcohol abuse, nonalcoholic steatohepatitis, and metabolic disease. The mutation landscape in liver carcinogenesis is reportedly complicated, involving a number of pathways as well as somatic mutations in a multitude of genes [ 2 , 3 , 4 ]. Among the genetic alterations, telomerase reverse transcriptase ( TERT ) promoter mutations were reported to occur early and most frequently, affecting approximately 30–60% of all HCC patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, embryonic stem cells and most cancer cells can maintain telomeres to overcome cell senescence or apoptosis. This process is controlled by TERT , the catalytic component of the telomerase complex that maintains telomere ends by addition of the telomere repeat TTAGGG [ 4 , 9 ]. Thus, TERT plays an important role in oncogenesis and the immortality of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the gene recurrently targeted by viral integration usually plays a role in carcinogenesis. TCGA analysis showed that TERT , MLL4 and CCNE1 have aberrant expressions in HCC, and their biological functions in hepatocarcinogenesis have been extensively studied 21,41,42 . On the contrary, except for TERT , the impacts of MLL4 and CCNE1 on NHL have never been documented.…”
Section: Discussionmentioning
confidence: 99%
“…TERT activation is shown in 85-90% of all human cancers. 34,35 TERT is the most frequently integrated gene by HBV-DNA in HCC. To date, 19 independent studies have identified a total of 435 integrations of HBV-DNA in the TERT gene, and 62.99% (274/435) of HBV-DNA integration occurs in the promoter region of TERT.…”
Section: Discussionmentioning
confidence: 99%